Re-sensitizing Ampicillin and Kanamycin-Resistant E. coli and S. aureus Using Synergistic Metal Micronutrients-Antibiotic Combinations - Garza-Cervantes, Javier Alberto; Meza-Bustillos, Jesus F.; Resendiz-Hernández, Haziel; Suárez-Cantú, Ivan A.; Ortega-Rivera, Oscar Antonio; Salinas, Eva; Escárcega-González, Carlos Enrique; Morones-Ramírez, Jose Ruben (Frontiers in Bioengineering and Biotechnology, 2020)
Due to the recent emergence of multi-drug resistant strains, the development of novel antimicrobial agents has become a critical issue. The use of micronutrient transition metals is a promising approach to overcome this problem since these compounds exhibit significant toxicity at low concentrations in prokaryotic cells. In this work, we demonstrate that at concentrations lower than their minimal inhibitory concentrations and in combination with different antibiotics, it is possible to mitigate the barriers to employ metallic micronutrients as therapeutic agents. Here, we show that when administered as a combinatorial treatment, Cu2+, Zn2+, Co2+, Cd2+, and Ni2+ increase susceptibility of Escherichia coli and Staphylococcus aureus to ampicillin and kanamycin. Furthermore, ampicillin-resistant E. coli is re-sensitized to ampicillin when the ampicillin is administered in combination with Cu2+, Cd2+, or Ni2. Similarly, Cu2+, Zn2+ or Cd2+ re-sensitize kanamycin-resistant Escherichia coli and Staphylococcus aureus to kanamycin when administered in a combinatorial treatment with those transition metals. Here, we demonstrate that for both susceptible and resistant bacteria, transition-metal micronutrients and antibiotics interact synergistically in combinatorial treatments and exhibit increased effects when compared to the treatment with the antibiotic alone. Moreover, in vitro and in vivo assays, using a murine topical infection model, showed no toxicological effects of either treatment at the administered concentrations. Lastly, we show that combinatorial treatments can clear a murine topical infection caused by an antibiotic-resistant strain. Altogether, these results suggest that antibiotic-metallic micronutrient combinatorial treatments will play an important role in future developments of antimicrobial agents and treatments against infections caused by both susceptible and resistant strains.